Penerapan Model Blavo (Blended Learning Audio Video) Pada Perkuliahan Bahasa Indonesia Di PGSD FKIP Universitas Lambung Mangkurat - Rizky Amelia (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
Students need to have various abilities to be able to face the era of the industrial revolution 4.0. The abilities and skills needed to be able to compete globally are constantly changing every decade. The FKIP Primary School Teacher Education Study Program of Lambung Mangkurat University has the same goal, namely to produce graduates who are educated, trained and skilled workers who meet the competencies required by the world of work in relevant education fields and have broad insights on the development of education. This study aims to explain the application of the BLAVO (Blended Learning Audio Video) model in Indonesian Language lectures at PGSD FKIP Universitas Lambung Mangkurat. This study uses a quantitative approach. The results showed that the lecture model that involved students in the learning process and was more present would be more interesting than the existing methods. BLAVO which combines Blogging and case-based learning is a combination of methods that involve students with current methods in which students will be more interested and passion for learning.